PENGARUH PEMAHAMAN AKUNTANSI, KECANGGIHAN TEKNOLOGI INFORMASI, PELATIHAN DAN PENGALAMAN KERJA TERHADAP KINERJA SIA MELALUI EFEKTIVITAS PENGGUNAAN SIA SEBAGAI VARIABEL INTERVENING PADA PT KAI (PERSERO) DAOP 8 SURABAYA - Faizati, Lutfika Arifa; Nugroho, Mulyanto; Arifin, Mochammad (LPPM Universitas Bina Bangsa, 2025)
The success of a company in modern business fundamentally depends on how effectively it utilizes the performance of its Accounting Information System (AIS). This is because AIS serves as a critical foundation for managing the company's financial data. This study aims to determine the extent to which accounting understanding, information technology sophistication, training, and work experience influence AIS performance, with the effectiveness of AIS utilization acting as an intervening or mediating variable. The research employs a quantitative approach, using a sample of 25 employees from the finance unit at PT KAI (Persero) operational area 8 Surabaya. The data is analyzed using the Partial Least Square (PLS) method. The findings reveal that accounting understanding, training, and work experience have a positive and significant effect on AIS performance. However, the variable of information technology sophistication does not significantly affect AIS performance. Furthermore, the mediation effect analysis shows that the effectiveness of AIS utilization does not mediate the relationship between accounting understanding, information technology sophistication, training, and work experience on AIS performance